Resonantly pumped bright triplet exciton lasing in caesium lead bromide perovskites - Ying, G; Farrow, T; Jana, A; Osokin, V; Shao, H; Park, Y; Taylor, R A (University of Oxford, 2021)
The research looks into the lasing phenomenon from the tetragonally symmetric CsPbBr3 perovskite nanocrystals. The emission has been demonstrated to originate from the triplet state via polarisation and lifetime verifications. A resonantly pumped excitation source has been adopted to tune the inter-level transition resonantly, which significantly enhances the emission characteristics. The data follows the order of the figures contained in the corresponding paper and a comment in each data file explains what each column of the data stands for. The data files cover all the experimental results presented in the main text of the paper.